Head-to-head ex vivo comparison of clinically used direct anticoagulant drugs - Fadraersada, Jaka; Alva-Gallegos, Raúl; Skořepa, Pavel; Musil, František; Javorská, Lenka; Matoušová, Kateřina; Krčmová, Lenka Kujovská; Paclíková, Markéta; Carazo, Alejandro; Blaha, Vladimír; Mladěnka, Přemysl (Naunyn-Schmiedeberg's archives of pharmacology, 2024)
An imbalance in coagulation is associated with cardiovascular events. For prevention and treatment, anticoagulants, currently mainly xabans and gatrans, are used. The purpose of the present study was to provide a head-to-head comparison since there are no studies directly evaluating these novel anticoagulants. An additional aim was to find whether selected anthropological and biochemical factors can affect their anticoagulant properties as they are used in fixed doses. In this cross-sectional study, blood from 50 generally healthy donors was collected, and coagulation responses to dabigatran, argatroban, rivaroxaban, and apixaban, at a concentration of 1 μM, were analyzed. Heparin was used as a positive control. Prothrombin time (PT) expressed as international normalized ratio (INR) and activated partial thromboplastin time (aPTT) were measured and compared. Rivaroxaban was the most active according to PT/INR while argatroban according to aPTT. The ex vivo anticoagulant effect measured by INR correlated inversely with body mass index (BMI) in all four anticoagulants tested. Shortening of aPTT was associated with higher cholesterol and triglyceride levels. No sex-related differences were observed in response to the anticoagulant treatments. As this was an ex vivo study and pharmacokinetic factors were not included, the influence of BMI is of high therapeutic importance.
Keywords: parciální tromboplastinový čas; Pipecolic Acids; lidé; Middle Aged; Adult; Prothrombin time; sulfonamidy; Anticoagulants; Activated partial thromboplastin time; Female; kyseliny pipekolové; pyridony; Partial Thromboplastin Time; Body Mass Index; rivaroxaban; Pyridones; dabigatran; Humans; hemokoagulace; index tělesné hmotnosti; Dabigatran; průřezové studie; Cross-Sectional Studies; Blood Coagulation; Lipid; lidé středního věku; arginin; mužské pohlaví; mladý dospělý; pyrazoly; protrombinový čas; Sulfonamides; Prothrombin Time; ženské pohlaví; Rivaroxaban; INR; Young Adult; Male; Body mass index; dospělí; Arginine; International Normalized Ratio; Pyrazoles; antikoagulancia